Eine Karte der Flächennutzung (1803-1820).: Als Beitrag zu einer Historischen Wirtschaftskarte der Rheinlande um 1820 - Hahn, Helmut (ERDKUNDE, 1967)
A working party called 'Economic map of the Rhine land around 1820’ founded by Professors H. Hahn (Social and Economic Geography), F. Petri (Local History) and W. Zorn (Social and Economic History) has been in existence since 1963 at the University of Bonn. Since then, the first results have been presented for discussion by W. Zorn and published from time to time in “Rheinische Vierteljahresblätter. At the moment, a map of land use (arable, pasture, heath and fallow, woodland, vineyards and bog) at a scale of 1 : 200 000 is being drawn, on the basis of the Tranchot-Müffling survey in the years between 1803 and 1820. The land use map of Regierungsbezirk Aachen (Suppl. V) is intended not only to present a first result of this work but at the same time to give an impression of the influence of natural and cultural spatial factors on land use. Further investigations of tillage conditions and animal husbandry have just begun.